Interleukin-22 Polymorphisms in Plasmodium falciparum-Infected Malaria Patients. (19th February 2020) - Aljarba, Nada H.; Al-Anazi, Mashael R.; Shafeai, Mohammed I.; Rudiny, Fuad H.; Bin Dajem, Saad M.; Alothaid, Hani; Darraj, Majid; Alkahtani, Saad; Alghamdi, Jahad; Al-Ahdal, Mohammed N.; Al-Qahtani, Ahmed A.
Abstract : Background and Objectives . Malaria infection, caused by Plasmodium falciparum, is the most lethal and frequently culminates in severe clinical complications. Interleukin-22 (IL-22) has been implicated in several diseases including malaria. The objective of this study was to investigate the role of IL-22 gene polymorphisms in P . falciparum infection. Material and Methods . Ten single-nucleotide polymorphisms (SNPs), rs976748, rs1179246, rs2046068, rs1182844, rs2227508, rs2227513, rs2227478, rs2227481, rs2227491, and rs2227483, of IL-22 gene were genotyped through PCR-based assays of 250 P . falciparum -infected patients and 200 healthy controls. In addition, a luciferase reporter assay was done to assess the role of the rs2227513 SNP in IL - 22 gene promoter activity. Results . We found that the rs2227481 TT genotype (odds ratio 0.254, confidence interval = 0.097-0.663, P = 0.002 ) and the T allele is associated with protection against P . falciparum malaria as well as the rs2227483 AT genotype (odds ratio 0.375, confidence interval = 0.187-0.754, P = 0.004 ). The haplotype A-T-T of rs1179246, rs1182844, and rs976748 was statistically more frequent in the control group (frequency 41%, P = 0.034 ) as well as the haplotype A-G of rs2046068 and rs2227491 (frequency 49.4%, P = 0.041 ). The variant rs2227513 G allele had a statistically higher activity (P < 0.0001 ) with the luciferase reporter assay. Conclusion . The study suggests that IL-22 polymorphisms in rs2227481 and rs2227483 could contribute to protection against P . falciparum malaria. Also, the G allele of rs2227513, located in the promoter region of IL - 22 gene, could be essential for higher expression levels of IL-22 cytokine.